PENERAPAN PERENCANAAN BIAYA DAN PENGENDALIAN BIAYA SEBAGAI ALAT AKUNTANSI PERTANGGUNGJAWABAN PERUSAHAAN (Studi Kasus Pada PT.Cesco Offshore and Engineering Batam) - Moko, Wahyu Ari Sudiat; Hamta, Firdaus; Santoso, Cahyo Budi (Universitas Riau Kepulauan, 2015)
ABSTRACTThis research for knows regarding implementation of cost planning and cost control as means of accounting liability at pt.Cescooffshore and engineering batam.This research based on the qualitative approach. The research also based on literature and interviewed with director at PT. CescoOffshore and Engineering to get data. Method of analyze this research is to analyze of implementation of cost planning andÂ cost control as means of accounting base on literature and interviewed.The result of this research on PT Cesco Offshore and Engineering, The company has been implementation of cost planning and cost control as means of accounting liability as well. The research can be detected by cost planning as structure organization, budget, cost classification, cost accounting system, report of liability. and cost control as cost standard, the budget, and also implementation of accounting liability as well.Â Keywords: cost planning, cost control and implementation of accountingliability